2020
DOI: 10.1093/toxsci/kfaa160
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen Modulates the Expression of Steroidogenesis-Associated Genes and Estradiol Levels in Human Placental JEG-3 Cells

Abstract: Acetaminophen is the only medication recommended for pain and fever management during pregnancy. However, studies have reported an association between in utero acetaminophen and neurocognitive disorders later in life. Additionally, acetaminophen has been shown to have endocrine disrupting properties altering hormones critical for normal fetal development. As the placenta is an endocrine organ that produces hormones for fetal development, any attempts to elucidate the mechanism underlying in utero acetaminophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Using drugs during pregnancy may affect the endocrine function of the placenta. For example, estradiol is crucial for the development of fetal reproductive organs, and acetaminophen can inhibit estradiol secretion in human placental cells, which suggests that prenatal acetaminophen exposure may affect gonad development by inhibiting placental estradiol secretion 95 .…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
“…Using drugs during pregnancy may affect the endocrine function of the placenta. For example, estradiol is crucial for the development of fetal reproductive organs, and acetaminophen can inhibit estradiol secretion in human placental cells, which suggests that prenatal acetaminophen exposure may affect gonad development by inhibiting placental estradiol secretion 95 .…”
Section: Multi-organ Developmental Toxicity In Offspring Induced By M...mentioning
confidence: 99%
“…In vivo, in vitro and ex vivo studies have shown that APAP directly perturbs hormone-dependent processes, including inhibition of androgen production and increased oestrogen production, disruption of steroidogenesis, depletion of sulfated sex hormones, perturbation of immune function, induction of oxidative stress and indirect activation of the endocannabinoid system 1,2,[61][62][63][64][65] . Independently of APAP, these processes have been implicated as mechanisms related to the development of neurodevelopmental [66][67][68][69][70][71][72][73][74][75][76] and reproductive disorders 2 .…”
Section: Nature Reviews | Endocrinologymentioning
confidence: 99%
“…Independently of APAP, these processes have been implicated as mechanisms related to the development of neurodevelopmental [66][67][68][69][70][71][72][73][74][75][76] and reproductive disorders 2 . In addition to potential effects on neuronal and reproductive development, a combination of clinical studies together with experimental work in animal models and cell lines has also suggested that APAP exposure during pregnancy might decrease fetal haematopoietic stem cell numbers alter steroidogenesis in the placenta and induce placental damage 65,[77][78][79][80] .…”
Section: Nature Reviews | Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, APAP increased pregnenolone, but impaired its subsequent conversion to progesterone by CYP17A1 ( Holm et al, 2015 ). APAP also modulated the expression of steroidogenic genes, leading to a significant dose-dependent decrease in estradiol secretion in human placental JEG-3 cells ( Addo et al, 2021 ). Furthermore, the anti-androgenic and anti-estrogenic activities of anti-inflammatory drugs (APAP, IBU, DCF, naproxen) at doses between 10 −6 and 10 −5 M have been demonstrated using two in vitro reporter-gene assays based on a CXCL12-expressing human T47 breast carcinoma cell line and ERα and AR-expressing recombinant yeast assays ( Ezechias et al, 2016 ).…”
Section: Effects Of Exposure To Nsaids and Apap In Vitro/ex...mentioning
confidence: 99%